Effect of alloying elements on stacking fault energy and softening/hardening of zirconium - L.C. Liu; J.T. Zheng; Z.P. Wu; Z.Y. Xu; S.F. Zhou (Journal of Materials Research and Technology)
First-principles calculations is used to comparatively study the effects of alloying element (Cr, Fe, Nb, Cu, and Sn) on phase stability, stacking faults energy, and solid-solution softening/hardening of 0001<112¯0> and {101¯0}<112¯0> slip systems of HCP Zr. Calculations reveal that the introducing Cr, Fe, Nb, and Cu, except Sn, would reduce the thermodynamic stability of Zr. In addition, the adding Sn would either raise or lower the stacking fault energy and ductility of HCP Zr, depending on the specific the slip system. And addition of Fe could hinder the dislocation movement and enhance the solid solution hardening of Zr. It is also demonstrated that the priority of dislocation motion along {101‾0}<112‾0> slip system remains unchanged with the incorporation of Cr, Fe, and Nb. Conversely, adding Sn would cause dislocation motion to preferentially follow the {0001}<112‾0> slip system. Compared with adding only Sn, the synergistic addition of Sn and Nb (Fe) can significantly improve the softening of Zr and reduce the stacking fault energy of Zr {0001}<112‾0> slip system. This study will provide deeper insights into the stacking fault energy and solid solution softening/hardening behaviors of Zr alloys.